Developing a play-anywhere handheld AR storytelling app using remote data collection - Raeburn, Gideon; Welton, Martin; Tokarchuk, Laurissa (Frontiers in Computer Science, 2022)
Immersive story experiences like immersive theatre and escape rooms have grown in popularity in recent years, many of which offer the audience an opportunity to take a more active role in events. Many of these experiences were forced to close at the start of the COVID-19 pandemic, arising from restrictions to group activities and travel. This created an opportunity for immersive experiences that users could take part in around their local neighbourhoods. Several mobile applications were developed for this research, aiming to make effective use of local map data, alongside virtual content overlaid on users' surroundings through Augmented Reality (AR), to provide story features not necessarily present in the user's real environment. An iterative design process was adopted to investigate whether the remote field testing of such apps, using participants' own devices at a variety of locations, could provide data of sufficient quality to improve the experience offered. This research describes not only the changes and new features tested across each app iteration, but also modifications made to the testing procedure. These aimed to both make sure each app was completed in the intended manner by those participating remotely, as well as to compare the effectiveness of different questionnaire measures and methods of feedback collection, relating to participants' levels of immersion and engagement. The testing procedure was also applied to a curated site-specific study using a new version of the app, forming a final user study after pandemic restrictions had eased. This combination of remote and later curated studies offered a reverse methodology to much previous research in this field, but was found to offer advantages not only in corroborating the results of the remote studies, but also in offering new insights to further improve such a play-anywhere AR story app. Such an app offers benefits to those who may prefer the opportunity to take part in such an activity solo or close to home, as well as for storytellers to have the freedom to develop an outside story for use anywhere by a potentially large number of users, without the challenges and costs in migrating it to different locations.